FAUNA SILVESTRE - Osorio, Director 5 Simp. For., Luis Fernando (Colombia forestal, 2012)
Comité científico del simposio Director Luis Fernando Osorio Vélez, Ph.D. Universidad Nacional de Colombia, sede Medellín. Colombia. Fauna silvestre Brian C. Bock, Ph.D. Universidad de Antioquia. Colombia. Jaime Polanía Vorenberg, Ph.D. Universidad Nacional de Colombia. Colombia. Joan Gastón Zamora Abrego, Ph.D. Universidad Nacional de Colombia. Colombia. Néstor Javier Mancera Rodríguez, Ph.D. Universidad Nacional de Colombia. Colombia. Sergio Solari, Ph.D. Universidad de Antioquia. Colombia.